Chest Pain after Blunt Trauma: Not Always Noncardiac - Mukesh Dhillon; Aditi Sharma; Vivek S Guleria; Ankit Kumar (Journal of Clinical and Preventive Cardiology)
Blunt trauma chest with concomitant injury to the heart is common. Its severity ranges from asymptomatic to cardiac rupture causing death. Coronary artery injury to the left anterior descending artery is more common than the right coronary artery owing to its position. Co-existing injuries when present confound diagnosis leading to delay. Therefore, a high index of suspicion and appropriate use investigations are key to diagnosing myocardial infarction (MI) in this setting. Apart from conservative medical management, options available for the treatment of such cases are fibrinolytic therapy, angioplasty, or coronary artery bypass grafting. Each option has its pros and cons, and there is no one-size-fits-all treatment option. Here, we describe a case of acute ST-elevation inferior wall MI in a healthy young man after blunt trauma to the chest, managed with angioplasty.